Computerized Accounting Information System on Financial Reporting of Deposit Money Banks in Nigeria - Timothy Aondona Aondover; Kayode Oluwafemi Ishola; Okonkwo Doris Ngozi (Rowter Journal, 2026)
This study examined the effect of Computerized Accounting Information Systems (CAIS) on the financial reporting of Deposit Money Banks in Nigeria. The study was motivated by the increasing adoption of computerized accounting technologies in the banking sector and the need to enhance the quality, accuracy, timeliness, reliability, and transparency of financial reporting. The study adopted a qualitative research approach based on the secondary method of data collection. Relevant information was obtained from textbooks, peer-reviewed journal articles, online publications, and other documented sources relating to computerized accounting information systems and financial reporting. The study was anchored on the Real Bills Doctrine Theory and the Anticipated Income Theory, which provide a theoretical basis for understanding banking operations and financial reporting practices. Findings from the reviewed literature revealed that computerized accounting information systems significantly improve the quality of financial reporting by enhancing information accuracy, timeliness, reliability, transparency, and decision-making efficiency. The study further found that information quality, user competence, service quality, and information technology are critical determinants of effective financial reporting in Deposit Money Banks. It concluded that the integration of computerized accounting systems enhances operational efficiency, strengthens internal controls, facilitates regulatory compliance, and improves stakeholder confidence in financial reports. The study therefore recommends that Deposit Money Banks should continue investing in advanced computerized accounting technologies, provide continuous training for accounting personnel to improve user competence, strengthen internal control mechanisms within computerized environments, and regularly upgrade their information technology infrastructure to sustain high-quality financial reporting and overall organizational performance.